Exploring age-related differences in metacognitive self-regulation: the influence of motivational factors in secondary school students - Katsantonis, Ioannis (Frontiers in Psychology, 2024)
Introduction: Metacognitive self-regulation is a crucial factor that promotes students' learning and achievement. However, the evidence regarding age differences in metacognitive skills is rather mixed, with some evidence pointing towards further refinement and development and other evidence suggesting declining levels. Academic motivation, an important antecedent of metacognitive selfregulation, has also been reported to decline steeply in adolescence. Hence, this raises the question whether there are any age differences in academic motivation and metacognitive self-regulation of adolescents and whether age differences in academic motivationes drive declines decreases in metacognitive self-regulation. Method: Α large sample size of 1027 Greek adolescents (ages 12 to 16, Mage=13.95, SD=.78) was utilised in the present study. Multigroup measurement invariance analyses were deployed to compare the latent means of motivational factors (self-efficacy, task value, mastery and performance goals) and metacognitive self-regulation across age groups. Cholesky decomposition was applied to test the independent contribution of motivational factors to and the indirect effects of age on metacognitive self-regulation. Results: Invariance analyses revealed scalar invariance for metacognitive self-regulation, language self-efficacy, mastery and performance goal orientations and partially scalar invariance for task value. Older adolescents scored lower on metacognitive self-regulation, less mastery and performance goals, and less self-efficacy. Older students scored lower on metacognitive selfregulation via indirect effects through Cholesky decomposed motivational factors. Discussion: Self-efficacy, mastery and performance goals, and task value are similarly understood across adolescents in different age groups. Decreased mastery and performance goals and task value can lead to reduced metacognitive self-regulation in adolescents. The implications of the findings underscore the key role of making students more engaged with lessons' content in order to promote greater academic motivation and prevent declines decreases in metacognitive self-regulation.